Effects of Garlic Clove, Neem and Eucalyptus Leaf Extract on Mating Behaviour, Oviposition and Adult Emergence of Pulse Beetle, Callosobruchus maculatus - Akter, S; Nahar, N; Rahman, M (Progressive Agriculture, 2014)
Experiments were conducted in the laboratory to study the effects of garlic clove, neem and eucalyptus leaf extracts on mating behaviour, oviposition and adult emergence of pulse beetle, Callosobruchus maculatus. Intensity of seed damage and weight loss of gram seeds were also recorded. The results showed that the mating frequency, mating duration, oviposition, adult emergence of pulse beetle and weight loss of gram seeds were reduced significantly after application of the extracts. Among the extracts, neem leaf extracts showed lowest mating frequency (1), mating duration (3.66 minutes), lowest number of laid eggs (27.33), adult emergence (11.67), seed damage (6.89%) and weight loss (2.53%). On the other hand, garlic clove extract showed highest mating frequency (1.67), mating duration (4.67 minutes), highest number of laid eggs (40.33), adult emergence (18.66), seed damage (9.63%) and weight loss (3.73%). In the same way eucalyptus leaf extract showed 2nd highest mating frequency (1.5), mating duration (4.5 minutes), eggs laid (38.67), adult emergence (15.67), seed damage (9.25) and seed weight loss (3.33%). Considering efficacy of all extracts, it was found that the order of toxicity was neem leaf extract>eucalyptus leaf extract> garlic clove extract. DOI: http://dx.doi.org/10.3329/pa.v18i2.18164 Progress. Agric. 18(2): 93 - 97, 2007